Analysis of Optimal Performance for Nonlinear Gantry Crane System using MOPSO with Linear Weight Summation Approach - Jaafar, Hazriq Izzuan; Abdullah, Abdul Rahim; Anuar , Mohamed Kassim; Mohd Aras, Mohd Shahrieel; Mohd Nasir, Mohamad Na'im; Sulaima, Mohamad Fani (2013)
This paper presents development of Multi-Objective Particle Swarm Optimization (MOPSO) with Linear Weight Summation (LWS) approach to make the GCS more efficient and effective. The purpose of using LWS is to control the desired trolley position and payload oscillation according to the settling time (Ts), steady-state error (SSE) and overshoot (OS). The effectiveness of variation in weight summation is observed to find the optimal performances of the system. It will be demonstrated that GCS is able to achieve the goals and able to move the trolley as fast as possible to the desired position with low payload oscillation.